2010
DOI: 10.1183/09031936.00176309
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pneumococcal serotype group on outcome in adults with bacteraemic pneumonia

Abstract: The influence of infecting serotype group on outcome in bacteraemic pneumococcal pneumonia remains unclear.We performed a prospective, 10-yr observational study in an 800-bed teaching hospital. 299 adults diagnosed with pneumonia whose blood cultures showed growth of Streptococcus pneumoniae were included in the study. High invasive disease potential (H) serotypes included serotypes 1, 5 and 7F, which served as a reference category, were compared with low invasive disease potential (L) serotypes (3, 6A, 6B, 8,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
51
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 26 publications
3
51
2
Order By: Relevance
“…Among the main problems hampering the choice of an appropriate empirical antibiotic treatment of S. pneumoniae infections are the current high levels of antimicrobial resistance. In the present study, overall levels of nonsusceptibility to oral benzylpenicillin (13.4%), amoxicillin (2%), cefotaxime (1%), erythromycin (12%), and levofloxacin (0.8%) in S. pneumoniae isolates from elderly patients with pneumonia were lower than the percentages of resistance described in other studies of pneumococcal pneumonia performed in Spain (7,14,30,31). Additionally, and in agreement with recent studies (10,24,31), the trend toward a decrease in nonsusceptible S. pneumoniae isolates seems to be continuing and is associated with a decrease in episodes of pneumonia caused by PCV7 serotypes.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Among the main problems hampering the choice of an appropriate empirical antibiotic treatment of S. pneumoniae infections are the current high levels of antimicrobial resistance. In the present study, overall levels of nonsusceptibility to oral benzylpenicillin (13.4%), amoxicillin (2%), cefotaxime (1%), erythromycin (12%), and levofloxacin (0.8%) in S. pneumoniae isolates from elderly patients with pneumonia were lower than the percentages of resistance described in other studies of pneumococcal pneumonia performed in Spain (7,14,30,31). Additionally, and in agreement with recent studies (10,24,31), the trend toward a decrease in nonsusceptible S. pneumoniae isolates seems to be continuing and is associated with a decrease in episodes of pneumonia caused by PCV7 serotypes.…”
Section: Discussioncontrasting
confidence: 50%
“…Several studies of pneumonia found that serotype 3, the most frequent serotype causing pneumonia in Spain, was very often associated with severe disease in the elderly (3,12,14). Although serotype 3 was isolated very frequently in the present study, both from patients with pneumonia and from those with AECOPD, it was isolated more often from patients with pneumonia.…”
Section: Discussioncontrasting
confidence: 41%
“…In particular, serotypes 1 and 19A are strongly associated with adult PPE. Pneumococcal serotype can have profound implications for the spectrum of clinical disease, and has been shown to influence 30-day mortality, invasive disease potential and disease severity [26,27]. To our knowledge, this is the only study in adults with CAP to investigate the relationship between pneumococcal serotype and both invasive and noninvasive pneumococcal PPE.…”
Section: Discussionmentioning
confidence: 94%
“…Most cases of empyema among Australian children are caused by serotypes 1, 3 and 19A, 23 which are believed to be particularly virulent and more likely to invade the pleural cavity. 24,25 The reported increase in serotypes 1, 3 and 19A among invasive isolates might explain the increase in empyema but not in pneumonia per se. [10][11][12] On the other hand, an increase in the incidence of empyema was observed in some studies before the introduction of the PCV7.…”
Section: Discussionmentioning
confidence: 99%